Pertumbuhan Ekonomi dan Lapangan Kerja Layak: Optimalisasi Social Media Marketing Tata Rias Desa Perajin - Pratiwi, Diany Putri; Pahalmas, Junior Zamrud; Karerek; Marleni; Trecy Austin (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2023)
Having a job does not guarantee the ability to get out of the clutches of poverty. A persistent lack of decent work opportunities, inadequate investment and low consumption lead to an erosion of the fundamental social contract that forms the basis of a democratic society: Putting job creation at the center of economic policy-making and development plans, will not only generate decent work opportunities but also stronger growth, and can reduce poverty. This is a positive circle that is good for the economy and for society and encourages sustainable development. Indonesia has made a very strong commitment to achieving decent work and is playing an important role in ensuring that employment and workforce issues are included in the Sustainable Development Goals (SDGs). The importance of decent work in achieving sustainable development is highlighted by its aim to promote sustainable economic growth, productive employment opportunities and decent work for all. Social media marketing is a form of digital marketing that uses social media to market business products or services through the platforms provided by the media. Today social media is media that cannot be separated in everyday life. This is related to the cosmetology business that the author introduces in community service in Desa Perajin.